Reviews - Shân Wareing; Peter Funnell; Brian Boullier; Heather Dalgleish; Kate Morss; Ray McAleese; Philip Barker (Research in Learning Technology, 1998)
Student motivation: the black box which concerns so many of us in higher education, and potentially the answer to all our problems. If we could crack this one, students would use the library and the Web and get their assignments in on time. They would come to our lectures and tutorials having prepared; they would ask interesting and challenging questions; and we would be able to reveal to them the excitement and charm of our chosen discipline. They would all pass everything, and the reputation of our institutions would increase. So does this book have the answers?